O processo de produção da cidade a partir das intervenções urbanas : o caso do "Projeto Lerner" para Serra-ES - Schaeffer, Luciana (2013)
The production process of the city is constant and changing, these features enabled, in large part, by the various agents that make up the urban space. Urban interventions accelerate the changes that are inherent in the city to understand the production process is desired to understand the relationships between these agents and their part in the articulation, development and implementation of an urban intervention. In this context, the objective of this dissertation is to study these relationships, taking as a case study of urban renewal project developed by the office of the architect Jaime Lerner "Contributions to Urban Sustainable Development of the Municipality of Serra", hired by the City of Serra-ES. Serra is an important city municipality in the Metropolitan Region of Vitória, both in terms of population, behind Vila Velha, and economically, its PIB is second only behind to the capital Vitória. Seerra is still undergoing a process of recent urban transformation, which highlights mainly the growth of gated communities. As a result, over all, it could be seen that the character "developmental" is still widely applied. In cities and Serra the construction of a fair and equitable urban space is confused with economic expansion, particularly in the Serra, the development of real estate capital, supported and promoted by the State and the urban interventions legitimizing these actions. It is intended, in conclusion, contribute to the understanding of the production of the city from an urban intervention that apparently is of interest to all segments of society, but just privileges the portion dominant of society. Therefore, it is expected that in future, this dissertation positively assist participation in urban production of all segments of society.